Microhomologies Are Associated with Tandem Duplications and Structural Variation in Plant Mitochondrial Genomes. (13th August 2020) - Xia, Hanhan; Zhao, Wei; Shi, Yong; Wang, Xiao-Ru; Wang, Baosheng
Abstract: Short tandem repeats (STRs) contribute to structural variation in plant mitochondrial genomes, but the mechanisms underlying their formation and expansion are unclear. In this study, we detected high polymorphism in the nad 7-1 region of the Pinus tabuliformis mitogenome caused by the rapid accumulation of STRs and rearrangements over a few million years ago. The STRs in nad 7-1 have a 7-bp microhomology (TAG7) flanking the repeat array. We then scanned the mitogenomes of 136 seed plants to understand the role of microhomology in the formation of STR and mitogenome evolution. A total of 13, 170 STRs were identified, and almost half of them were associated with microhomologies. A substantial amount (1, 197) of microhomologies was long enough to mediate structural variation, and the length of microhomology is positively correlated with the length of tandem repeat unit. These results suggest that microhomology may be involved in the formation of tandem repeat via microhomology-mediated pathway, and the formation of longer duplicates required greater length of microhomology. We examined the abundance of these 1, 197 microhomologies, and found 75% of them were enriched in the plant mitogenomes. Further analyses of the 400 prevalent microhomologies revealed that 175 of them showed differential enrichment between angiosperms and gymnosperms and 186 differed between angiosperms and conifers, indicating lineage-specific usage and expansion of microhomologies. Our study sheds light on the sources of structural variation in plant mitochondrial genomes and highlights the importance of microhomology in mitochondrial genome evolution.